The thing on the wing can sing : a short vowel sounds book with consonant digraphs - Cleary, Brian P., 1959-; Miskimins, Jason (Minneapolis, MN : Millbrook Press, 2009)
A short vowel sounds book, including consonant digraphs, with rhyme, repetition, illustrations, and phonics to aid learning.
2.0
K-3
Keywords: English language -- Consonants -- Juvenile literature; English language -- Phonetics -- Juvenile literature; English language -- Vowels -- Juvenile literature; Reading -- Phonetic method -- Juvenile literature; English language -- Consonants; English language -- Phonetics; English language -- Vowels; Reading -- Phonetic method; English language; English language -- Pronunciation; Reading -- Phonetic method; Readers (Elementary).